Tashmim al-Mauqi’ al-Ta’limi Muassasan ‘ala at-Tahlil at-Taqabuli li Tanmiyati Maharati al-Kitabah li Thullab al-Fashl al-Dirasi al-Khamis bi Qismi Ta’lim al-Lughah al-‘Arabiyyah fil al-Jami’ah al-Islamiyyah al-Hukumiyyah Bone - Rahmat Hidayat Lubis; Zulkifli Hayad Hayad; Maulana Ashari (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2021)
The Arabic Language Education Study Program at the Bone State Islamic Institute is a study program that teaches four Arabic language skills, including writing skills. However, most of the students are alumni of non-Islamic boarding schools or Islamic boarding schools who do not get used to learning and practicing language in them, so it takes more time than the specified number of material meetings insya'. Not only additional time for study is needed, but the material is specially prepared and in accordance with the educational background of the 5th semester PBA study program students of IAIN Bone, such as material, insya', which is compiled based on contrastive analysis. Therefore, it is important for researchers to design a learning website based on contrastive analysis to improve the writing skills of 5th semester students of the Bone State Islamic Institute of Religion. Based on this, this study aims to: (1) Determine the characteristics of the learning website based on contrastive analysis to improve the writing skills of 5th semester students of the Bone State Islamic Agama Institute. (2) Knowing the feasibility of the learning website. (3) Knowing the effectiveness of the learning website. This research is a type of Research and Development (R&D) and True Experimental Design research in the form of Non Equavalent Control Group. In collecting data, researchers used interviews, tests, questionnaires, and documentation. And to analyze the data collected, the researcher used qualitative data analysis using Miles and Huberman's analysis of the Independent Sample t-test formula with the help of SPSS. From this research, it can be concluded that: (1) The characteristics of the learning website developed with the Dick & Cerry design model, and the learning achievement of this website is that after students finish learning on this website, students can write simple and systematic essays on topics familiar to them by putting together sentences. -broad sentences, this learning website material is prepared based on contrastive analysis, and specifically for students whose writing skills are still at the basic level. (2) It is known that this learning website is proven to be worthy of being seen from the results of the expert assessment of 85.5%, 95.8% one by one, 95.8% small group, field experiments and the average student assessment results of pre-test 62.3 and posttest 72.2. (3) It is known that this learning website has proven to be effective as seen from the results of the t-test sig value. (2-Tailed) 0.000 smaller than the standard significant t-table 5% = 0.05. With this, the researcher hopes that this learning website will be used as additional or alternative learning on the Insha' material for students who have the same characteristics as the characteristics of learning website users.